Status Matters: The Asymmetric Effects of Supervisor–Subordinate Disability Incongruence and Climate for Inclusion - Dwertmann, David J. G.; Boehm, Stephan A. (Academy of Management Journal, 2016)
Growing workforce diversity increases the likelihood that supervisors and subordinates will differ along demographic lines, a situation that has important implications for their relationship quality and individual outcomes. In a sample of 1,253 employees from 54 work units, we investigate the effects of differences in disability status between supervisors and subordinates on leader–member exchange (LMX) quality and subsequent performance ratings, and find that incongruence in general is related to lower LMX quality and lower performance. In addition, we propose and find an asymmetrical effect of disability incongruence, such that LMX quality is worse in dyads in which the supervisor has a disability than in dyads in which the subordinate has a disability. Furthermore, we investigate the moderating role of unit-level climate for inclusion on this relationship and find support for a buffering effect of inclusive climates on the negative incongruence-LMX relationship for scenarios in which the supervisor, but not the subordinate, has a disability. We build relevant theory for the relational demography, disability, LMX, and organizational climate literatures by predicting these effects on the basis of status mechanisms. These findings have important practical implications, as they provide companies with a feasible way to manage their diverse workforce.